CLOUD NATIVE OBSERVABILITY WITH OPENTELEMETRY learn to gain visibility into systems by... combining tracing, metrics and logging with opente. - BOTEN, ALEX (PACKT PUBLISHING LIMITED, 2022)
Leverage OpenTelemetry's API, libraries, tools and the collector to produce and collect telemetry along with using open-source tools to analyze distributed traces, check metrics and logs, and gain insights into application health Key Features Get to grips with OpenTelemetry, an open-source cloud-native software observability standard Use vendor-neutral tools to instrument applications to produce better telemetry and improve observability Understand how telemetry data can be correlated and interpreted to understand distributed systems Book Description Cloud-Native Observability with OpenTelemetry is a guide to helping you look for answers to questions about your applications. This book teaches you how to produce telemetry from your applications using an open standard to retain control of data. OpenTelemetry provides the tools necessary for you to gain visibility into the performance of your services. It allows you to instrument your application code through vendor-neutral APIs, libraries and tools. By reading Cloud-Native Observability with OpenTelemetry, you'll learn about the concepts and signals of OpenTelemetry - traces, metrics, and logs. You'll practice producing telemetry for these signals by configuring and instrumenting a distributed cloud-native application using the OpenTelemetry API. The book also guides you through deploying the collector, as well as telemetry backends necessary to help you understand what to do with the data once it's emitted. You'll look at various examples of how to identify application performance issues through telemetry. By analyzing telemetry, you'll also be able to better understand how an observable application can improve the software development life cycle. By the end of this book, you'll be well-versed with OpenTelemetry, be able to instrument services using the OpenTelemetry API to produce distributed traces, metrics and logs, and more. What you will learn Understand the core concepts of OpenTelemetry Explore concepts in distributed tracing, metrics, and logging Discover the APIs and SDKs necessary to instrument an application using OpenTelemetry Explore what auto-instrumentation is and how it can help accelerate application instrumentation Configure and deploy the OpenTelemetry Collector Get to grips with how different open-source backends can be used to analyze telemetry data Understand how to correlate telemetry in common scenarios to get to the root cause of a problem Who this book is for This book is for software engineers, library authors, and systems operators looking to better understand their infrastructure, services and applications by leveraging telemetry data like never before. Working knowledge of Python programming is assumed for the example applications that you'll be building and instrumenting using the OpenTelemetry API and SDK. Some familiarity with Go programming, Linux, and Docker is preferable to help you set up additional components in various examples throughout the book.